আগরতলা মামলার আনুচ্চারিত ইতিহাস ও শহীদ সার্জেন্ট জহুরুল হক - মিমি, নাজনীন হক; হোসেন, আবু মোঃ দেলোয়ার (ঢাকা: জার্নিম্যান বুকস্‌, 2015)
Transcript of interviews chiefly with accused politicians of 1968 political conspiracy case, on their experience of this sedition case; includes articles on Jahurūla Haka, 1935-1969, one of the accused in the Agartala Conspiracy Case.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৪৯৩) অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Huq, Zahurul, -- 1935-1969.; Trials (Conspiracy) -- Bangladesh -- Interviews; Politicians -- Bangladesh -- Interviews